2009
DOI: 10.1177/112070000901900412
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Repair of Chronic Tears of the Hip Abductor Mechanism

Abstract: Lateral sided hip pain frequently presents to the orthopaedic clinic. The most common cause of this pain is trochanteric bursitis. This usually improves with conservative treatment. In a few cases it doesn't settle and warrants further investigation and treatment. We present a series of 28 patients who underwent MRI scanning for such pain, 16 were found to have a tear of their abductors. All 16 underwent surgical repair using multiple soft tissue anchors inserted into the greater trochanter of the hip to reatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
91
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(98 citation statements)
references
References 15 publications
4
91
0
3
Order By: Relevance
“…It can cause gait dysfunction and pain. The described treatments for this condition are inconsistently successful [4,5,9,11,14,16]. The current study demonstrated, in both the laboratory and clinical setting, the TFL and anterior portion of the gluteus maximus were conveniently positioned for transfer to the greater trochanter to substitute for deficient gluteus medius and minimus muscles.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…It can cause gait dysfunction and pain. The described treatments for this condition are inconsistently successful [4,5,9,11,14,16]. The current study demonstrated, in both the laboratory and clinical setting, the TFL and anterior portion of the gluteus maximus were conveniently positioned for transfer to the greater trochanter to substitute for deficient gluteus medius and minimus muscles.…”
Section: Discussionmentioning
confidence: 60%
“…Spontaneous complete avulsion of the abductor muscles of the hip or avulsion as a complication of chronic trochanteric bursitis may cause severe limp and often is accompanied by pain [3,5]. Simple repair of the abductor tendons and muscle often is successful [4,9,14], but the failure rate is high [5,11,16], leaving deficiencies in the muscle and tendon that cannot be repaired with direct suturing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, the open technique has championed a high level of patient satisfaction with objective merits such as quantifiable improvements in abductor tendon strength and gait [12,[29][30][31]. In 2009, Voos et al [4,32] [1].…”
Section: Treatmentmentioning
confidence: 99%
“…Open repair techniques have included repairs using both transosseous sutures 6 and suture anchors. 8 Few reports have been published on the outcomes of open repairs. The collective series of studies suggests that most patients respond favorably.…”
mentioning
confidence: 99%